Analysis of students’ error in intuitive thinking test - H Hasanah; Y S Kusumah; B A Priatna (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study aims to determine and analyze students' mistakes in working out the problems of intuitive mathematical thinking. This research uses a descriptive qualitative method. The subject in this research are 8th grade students in junior high school. The data in this study was mathematical tests to show intuitive thinking ability. The results in this study showed that students' intuitive thinking is visible, but students’ intuitive thinking should be improved by providing a good understanding of learning topics.